From the given recurrence, it follows that
![a_(n+1) = 2a_n + 1 \\\\ a_(n+1) = 2(2a_(n-1) + 1) = 2^2a_(n-1) + 1 + 2 \\\\ a_(n+1) = 2^2(2a_(n-2)+1) + 1 + 2 = 2^3a_(n-2) + 1 + 2 + 2^2 \\\\ a_(n+1) = 2^3(2a_(n-3) + 1) + 1 + 2 + 2^2 = 2^4a_(n-3) + 1 + 2 + 2^2 + 2^3](https://img.qammunity.org/2022/formulas/mathematics/high-school/y836qop7xizosodzwypt8zrk81ow28elhf.png)
and so on down to the first term,
![a_(n+1) = 2^na_1 + \displaystyle \sum_(k=0)^(n-1)2^k](https://img.qammunity.org/2022/formulas/mathematics/high-school/oy53a3qjs6yzwy6q815poawyo2l6svl26y.png)
(Notice how the exponent on the 2 and the subscript of a in the first term add up to n + 1.)
Denote the remaining sum by S ; then
![S = 1 + 2 + 2^2 + \cdots + 2^(n-1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/454jmjqhvcl189vok620gx2yso2f35nelw.png)
Multiply both sides by 2 :
![2S = 2 + 2^2 + 2^3 + \cdots + 2^n](https://img.qammunity.org/2022/formulas/mathematics/high-school/7fu17ynowy89o29z359xpk76kotrfuh7ls.png)
Subtract 2S from S to get
![S - 2S = 1 - 2^n \implies S = 2^n - 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/cz3qt7pbeknmpnvr0i5rs43o12samkyppy.png)
So, we end up with
![a_(n+1) = 4\cdot2^n + S \\\\ a_(n+1) = 2^2\cdot2^n + 2^n-1 \\\\ a_(n+1) = 2^(n+2) + 2^n - 1 \\\\\implies \boxed{a_n = 2^(n+1) + 2^(n-1) - 1}](https://img.qammunity.org/2022/formulas/mathematics/high-school/xseb57b4wcldd49pe86dn5y376sexjb1x4.png)